INFLUENCE OF IFRS APPLICATION, SOLVENCY AND COMPANY SIZE ON THE TIMELINESS OF FINANCIAL REPORTING IN PROPERTY AND REAL ESTATE COMPANIES ON THE INDONESIAN STOCK EXCHANGE PERIOD 2020-2022 - Widayati, Widayati (Fakultas Ekonomi Prodi Akuntansi, 2024)
Financial reporting is a means for companies to convey various information. Timeliness is a way to measure the quality and transparency of financial reporting when financial information is announced. This research serves to test and prove the effect of implementing IFRS, solvency and company size on the timeliness of financial reporting. This research focuses on companies properties and real estate listed on the Indonesian Stock Exchange in 2020-2022 with a population of 64 companies. The sampling method was purposive sampling, so that a total sample of 72 companies was obtained. The data analysis technique used by researchers is logistic regression analysis. The research results show that the implementation of IFRS has a positive and insignificant effect, solvency the negative effect is not significant and company size has a significant positive effect on the timeliness of financial reporting. The value of the coefficient of determination (Nagelkerke R Squeare) is 0.127, this shows that the effect of implementing IFRS, solvency and company size was 12.7% while the remaining 87.3% was explained by factors other than the factors proposed in this research.